Docetaxel Enhances the Expression of STING Protein in PC3 Cells, and cGAMP Attenuates this Effect - Salimi, Shaghayegh; Rezaei, Mitra; Mousavi, Zahra; Atabakhshian, Roya; PourIran, Ramin; Ziai, Seyed Ali (Novelty in Biomedicine, 2020)
Background: The stimulator of interferon genes (STING) agonist (cGAMP) kills the cancer cells through the activation of the innate immune system. PC3 cells are high in BTK and low in STING. In this study, the effect of adding STING agonist, cGAMP, to docetaxel investigated. Materials and Methods: PC3 cells were treated with docetaxel, cGAMP, and a combination of the docetaxel and cGAMP. Cell toxicity was evaluated by MTT assay, and changes of STING, IRF3, BTK, and DDX41 genes’ expression were quantified by the real-time PCR. STING protein was also detected by Western blotting. Results: The IC50 of docetaxel was 31.1 nM, and cGAMP did not change it significantly but decreased docetaxel toxicity about 30%. Docetaxel increased IRF3, BTK, and DDX41 gene expression significantly, and STING protein about 5 folds. By adding cGAMP to docetaxel STING, IRF3, and BTK, expression decreased several folds. Conclusion: In this in vitro study, cGAMP potentiated docetaxel’s effects and alleviated it.